Cultivating Discipline and Independent Character Through the Implementation of the School Literacy Movement - zahidi, Syukron; Ebi Praheto, Biya (Universitas Negeri Surabaya, 2024)
Literacy skills as well as the character of discipline and independence are important for student learning success. This study aims to describe the implementation of GLS in fostering discipline and independence in grade 3 elementary schools. This research method uses a qualitative approach. The subjects of the study were 29 3rd grade elementary school students in Purworejo, Central Java. The data collection techniques used are observation, interviews, questionnaires, and documentation. This study uses triangulation of sources and methods to support the validity of the data. The data analysis technique used in this study is an interactive model from Miles, Huberman, & Saldana which consists of three main stages, namely data reduction, data presentation, and conclusion drawn/data verification. The results of the study show that the implementation of GLS in elementary schools can create various forms of literacy activities, namely creating reading corners, writing reflections on literacy activity books, activating school wall magazines, creating and appreciating poems and rhymes as well as writing book reviews or synopsis, and reading reading books for 15 minutes at the 0th hour. The implementation of GLS can foster the character of discipline and independence in students. For discipline character, 84% of students in the category are excellent on the indicator of completing tasks on time, 72% on the indicator of complying with existing regulations, and 92% on the indicator of good behavior. For independent character, 72% of students in the category are very good on the initiative indicator, 82% on the confidence indicator, and 88% on the responsibility indicator. In conclusion, the implementation of GLS in elementary schools can foster the character of discipline and independence in students.